THE CIRCULAR ECONOMY HANDBOOK, REALIZING THE CIRCULAR ADVANTAGE, BY PETER LACY, JESSICA LONG, WESLEY SPINDLER, A BOOK REVIEW - Bašić, Jasmina; Jovčić, Ljiljana; Janić, Lazar (Economics of Agriculture, 2020)
The paper prepared in the form of a book review is a review of the book written by the authors Peter Lacy, Jessica Long and Wesley Spindler. The book is entitled "The Circular Economy Handbook, Realizing the Circular Advantage". The book was published by Palgrave Macmillan in 2020. Apart from their academic background, the authors of the book are world-acknowledged experts experienced in leading the worlds largest circular economy and sustainability strategy programs and studies, advising the senior leaders of the Fortune 500 companies and public organizations towards zero-waste policies and the circular economy. The book was written as a support to the effort made by the World Economic Forum, the Forum of Young Global Leaders, the Platform for Accelerating the Circular Economy (PACE) in the development of the circular economy and the forewords in the book were written by PACEs C.E.O. and other program co-founders and the world-known thought leaders in those specialized fields.